2016
DOI: 10.15344/2455-3867/2016/113
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction Reasons and Solutions from the Perspective of Sultan Qaboos University Undergraduates: A Qualitative Study

Abstract: Because the researchers had the opportunity to teach courses at SQU, they were able to observe the strong relation with and heavy use of Smart phones among SQU undergraduates. These students used their devices when they were walking around, during classes and even when they were eating in the cafeteria. For many reasons SQU students can develop Smartphone addiction. First, Smart phones have functions that enable students to avoid communicating with others face-to-face

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
5
21
0
1
Order By: Relevance
“…There was also a significant positive correlation between smartphone use and insomnia in the current study, in line with previous literature that reported smartphone addiction was associated with poor sleep quality (Demirci et al, 2015;Sahin et al, 2013). The average score of smartphone addiction scale was 83.9 (SD = 30.4); which is similar to a previous study conducted among university students at Sultan Qaboos University (AlBarashdi et al, 2016). There is inconsistency in previous research findings; that is, university students in previous research scored less compared with their counterparts in the current study (Choi et al, 2015;Demirci et al, 2015) and some other (Enez Darcin et al, 2016) is higher compared with the current study findings.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…There was also a significant positive correlation between smartphone use and insomnia in the current study, in line with previous literature that reported smartphone addiction was associated with poor sleep quality (Demirci et al, 2015;Sahin et al, 2013). The average score of smartphone addiction scale was 83.9 (SD = 30.4); which is similar to a previous study conducted among university students at Sultan Qaboos University (AlBarashdi et al, 2016). There is inconsistency in previous research findings; that is, university students in previous research scored less compared with their counterparts in the current study (Choi et al, 2015;Demirci et al, 2015) and some other (Enez Darcin et al, 2016) is higher compared with the current study findings.…”
Section: Discussionsupporting
confidence: 77%
“…The 21st century has witnessed an increase in the number of people using technology, especially the smartphone. The smartphone, with its installed applications and internet connection, has become an integral part of any person's daily activities (AlBarashdi et al, 2016;Sebastian & Jinesh, 2018). Social media, entertainment and business applications enable people to complete their work more efficiently and make communication between them easier and faster (Aljomaa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They mostly accessed the internet using their mobile phones, which made it an inseparable part of their daily life. Keeping the mobile phones turned on possibly made it easier for them to access the internet anytime and from anywhere ( AlBarashdi et al, 2016 ; Tenzin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This high prevalence of smartphone addiction among Nigerian pre-service mathematics teachers can be ascribed to their uncontrollable use of smartphones which culminated in their addiction. According to AlBarashdi, Bouazza, Jabur and Al-Zubaidi (2016) people are more prone to smartphone addiction because of psychosomatic and emotive problems such as downheartedness, lonesomeness, impulsivity, social anxiety, and interference. Although clinical tests were not conducted on the Nigerian sample to know the level of complicity in these problems, Nigerian pre-service mathematics teachers might be addicted to smartphone usage to ward off these problems.…”
Section: Volume 4 Issuementioning
confidence: 99%